Continuous Versus Pulsed Pure-Tone Audiometry in a Group of School-Aged Children - Catherine van Dijk; Naeema Osman (South African Journal of Communication Disorders, 2008)
Pure-tone testing is the primary audiological test procedure for the differential diagnosis of hearing loss and hearing disorders in school-aged children. No research is currently available internationally for children's responses to continuous versus pulsed pure-tones. The aim of this exploratory investigation was to compare the performance of a group of school-aged children on continuous versus pulsed pure-tone audiometry. The aims were to determine whether a threshold difference existed between continuous versus pulsed pure-tones and to record whether a listener preference existed between continuous versus pulsed tones for the frequency range of 125 to 8 000 Hz. Eighteen children (36 ears) aged between 8-12 years, participated in a hearing evaluation as well as in a brief three-question interview. Descriptive statistics viz. average threshold, mean difference and standard deviation of thresholds were used to analyse data. Listeners' perceived preferences were calculated in percentages and reasons for preferring one signal over another was analysed qualitatively. Although the automatically pulsed tone threshold (averaged a cross the frequencies tested) was lower than for the continuous tone, the difference was only 0.2 dB in the left ear and 0.5 dB in the right ear. This small difference is not important in clinical applications for which 5dB in crements are used in pure-tone audiometry. Where a listener preference was indicated, however, the continuous tones w ere preferred over pulsed tones by 56% percent of subjects. These findings differ from similar studies involving adults. This revealed that children may yield different preferences during pure-tone testing than adults and that these preferences should be taken into consideration during testing.